Mindfulness as a cognitive–emotional segmentation strategy: An intervention promoting work–life balance. Issue 4 (14th June 2014) - Michel, Alexandra; Bosch, Christine; Rexroth, Miriam
<x xml:space="preserve">Abstract</x> Employees struggling with work‐related cognitions, emotions, and associated energy levels during non‐work time can find their private roles impaired and work–life balance derogated. To reduce unwanted psychological preoccupation with work concerns, boundary theory suggests employees find their ideal way to integrate or segment both life domains. In this study, the authors design and evaluate an intervention teaching mindfulness as a cognitive–emotional segmentation strategy to promote work–life balance. They use a randomized waitlist control group design to evaluate effects of a 3‐week online self‐training intervention, with 246 employees participating at pre‐ and post‐test, and 191 participating at a 2‐week follow‐up. As expected, experimental group participants, compared with control group participants, experienced significantly less strain‐based work–family conflict and significantly more psychological detachment and satisfaction with work–life balance. Practitioner points Mindfulness, a cognitive–emotional segmentation strategy, enables employees to balance between work and private life. Voluntary organizational health and work–life balance programmes should include low‐cost but effective brief mindfulness interventions.